Faktor Determinan Earnings Response Coefficient pada Perusahaan Energy - Sukendra, Christian; Suhendah, Rousilita (Penerbit Goodwood, 2024)
Purpose: This study aimed to determine the influence of the leverage, growth opportunity, and firm size on Earnings Response Coefficient (ERC) on the energy companies listed on the Indonesia Stock Exchange from 2018 to 2022 Methodology/approach: This research approach used quantitative research with descriptive research type. The research sample was determined by purposive sampling method to obtain 47 energy companies listed on the Indonesia Stock Exchange in 2018-2022. The independent variables used in this study are leverage, growth opportunity, and firm size. Earnings Response Coefficient serves as the dependent variable in this research. This study employs panel data with a Fixed Effect Model regression. The data used has passed the classical assumption tests. Results/findings: The study results show that the growth opportunity has a positive and significant influence on the earnings response coefficient. However, the leverage and firm size do not have affect on the the earnings response coefficient. Limitations: This study has limitations as it was conducted only in the energy sector listed on the Indonesia Stock Exchange, with an observation period of five years. The independent variables used are leverage, growth opportunity, and firm size. The Earnings Response Coefficient, as the dependent variable, is measured by regressing unexpected earnings against cumulative abnormal returns. Future research is expected to use other independent variables, such as capital structure, conservatism, and earnings persistence. Contribution: This research can be used for adding knowledge in the financial field, especially for those who want to invest in a company by analyzing the Earnings Response Coefficient, which reflects the market's reaction to the company's earnings. This study contributes by showing that investors pay more attention to a company's growth opportunity when evaluating its earnings. This is because growth opportunity reflect the company's potential to generate profits. Investors are more interested when the company's profits are distributed in the form of dividends. However, investors also do not overlook other factors that could lead to speculation, which may impact the company's earnings.